Dropshipper responsibility in case of damaged goods in e-commerce transactions - Reni Astutik; Sunarjo Sunarjo; I Gusti Ngurah Adnyana; Dewi Ayu Rahayu; Mohammad Fahrial Amrulla; Ferry Anggriawan; Ariyanti Ariyanti; Fadilla Dwi Lailawati (University of Merdeka Malang, 2022)
Dropshipping is a buying and selling system where the drop shipper sells products that he doesn't own. Dropshipping is basically buying and selling that is carried out between sellers and buyers using internet media. The dropshipper only has photo samples of the supplier's goods, usually in the form of photos, which are then marketed to consumers at a price determined by the dropshipper, if sold, the dropshipper buys goods from the supplier by asking the supplier for help sending the goods to consumers on behalf of the dropshipper shop. Thus, in carrying out dropshipping buying and selling transactions, it involves parties, namely suppliers and dropshippers. E-commerce has recently been favored by producers both large and small as well as retail sellers in general. This is because promotion through online media is easier to reach consumers in terms of introducing or selling their products. E-commerce makes it easier for consumers and producers to make transactions. A dropshipper is a party that advertises goods, sells goods without owning the goods through his online shop, which then organizes so that the ordered goods are sent directly from the supplier to the consumer. Suppliers or also known as vendors are the owners of goods whose role in dropshipping is to send goods directly to buyers.